6-year treatment follow-up with an extended-release alkaline formulation (Sibnayal®) in primary distal renal tubular acidosis - Aurélia Bertholet-Thomas; Aurélie De Mul; Julie Bernardor; Gwenaëlle Roussey-Kesler; Ludmila Podracka; Robert Novo; François Nobili; Bertrand Knebelmann; Jérôme Harambat; Emilija Golubovic; Olivia Boyer; Massimo Di Maio; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Distal renal tubular acidosis (dRTA) is a rare disease characterized by hyperchloremic metabolic acidosis affecting growth, bone and kidney health. Methods The aim of B22CS study was to evaluate long-term safety and efficacy (anthropometric/pubertal, tubular damages/kidney function, bone biomarkers, compliance assessments) of Sibnayal®, a prolonged-release alkalinizing formulation with twice daily dosing, in children and adults with dRTA. All patients were previously included in the pivotal B21CS study, so were already receiving Sibnayal® when included in B22CS open-label follow-up study. Results A total of 30 patients with primary dRTA (mean age:10.6 ± 6.0 years) entered this long-term study (average of 6 years). At inclusion, most patients had adequate metabolic control, normal kidney function and height. Sibnayal® was well tolerated over the study duration.The most frequent adverse event was hypovitaminosis D (13 patients). Causality to treatment was reported for only 4% of all TEAEs (6 patients) and were mostly gastrointestinal. All adverse events resolved without treatment discontinuation. Sibnayal® allowed a sustained control of metabolic acidosis as plasma bicarbonate level was 22.0 ± 3.2 mmol/L at baseline versus 22.6 ± 2.5 mmol/L at the End of Follow-up (EoF), p = NS. From baseline to EoF, mean Z-score height significantly increased (-0.6 ± 1.0 to -0.3 ± 1.0, p = 0.03), without significant change in weight and body mass index. Kidney function remained stable from baseline to EoF: estimated glomerular filtration rate = 105 ± 17 and 104 ± 20 mL/min/1.73m2, respectively, p = NS. Urinary ratios: Calcium/Creatinine (UCa/UCr), Citrate/Creatinine (UCi/UCr), Calcium/Citrate (UCa/UCi) were not significantly different between baseline and EoF (p = NS). Mean lumbar bone mineral density Z-score significantly increased from baseline (-1.1 ± 1.0) to EoF (-0.8 ± 1.0), p = 0.005, with significant improvement between baseline and EoF in pre- and post-pubertal patients (p = 0.035 and p < 0.001, respectively), whilst it was maintained in pubertal patients (p = NS). Conclusion Long-term data support the good safety and efficacy profile of Sibnayal® in the treatment of dRTA with adequate control of metabolic acidosis, stable kidney function and significant positive long-term clinical outcomes.